2011
DOI: 10.1016/j.jconrel.2011.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-releasing porous polymethylmethacrylate/gelatin/antibiotic constructs for craniofacial tissue engineering

Abstract: An antibiotic-releasing porous polymethylmethacrylate (PMMA) construct was developed to maintain the bony space and prime the wound site in the initial step of a two-stage regenerative medicine approach toward reconstructing significant bony or composite craniofacial tissue defects. Porous polymethylmethacrylate (PMMA) constructs incorporating gelatin microparticles (GMPs) were fabricated by the sequential assembly of GMPs, the antibiotic colistin, and a clinically used bone cement formulation of PMMA powder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 43 publications
(74 reference statements)
1
53
0
Order By: Relevance
“…As bending is a combination of compression and tension, it is deduced that gelatin micro-particles might cause weakening in the PMMA tensile strength. Our finding was also supported by previous studies of PMMA/gelatin/antibiotic constructs used for craniofacial tissue materials [20]. It should also be noted that the decrease of the bending strength was detected within a relatively narrower range of particle density and size than what was reported in the literature as our cement mixture was designed to be injectable [20,30,31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As bending is a combination of compression and tension, it is deduced that gelatin micro-particles might cause weakening in the PMMA tensile strength. Our finding was also supported by previous studies of PMMA/gelatin/antibiotic constructs used for craniofacial tissue materials [20]. It should also be noted that the decrease of the bending strength was detected within a relatively narrower range of particle density and size than what was reported in the literature as our cement mixture was designed to be injectable [20,30,31].…”
Section: Discussionsupporting
confidence: 88%
“…Gelatin micro-particles could also be mixed with antibiotic or other therapeutic agents to promote regenerated tissue constructs and to achieve local controlled drug release [18][19][20]. The early clinical study showed reduction of 50 % leakage after the gelatin addition [1].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Previous work from our laboratory has utilized particulate delivery systems, such as gelatin and poly(DL-lactic-co-glycolic acid) (PLGA) microparticles, to control the release of antibiotics from porous PMMA-based constructs. [7,8] The porosity of these constructs was generated by using a carboxymethylcellulose or gelatin hydrogel as a porogen, and the resulting porosity allowed for greater cumulative release of antibiotic. [7][8][9][10] In these studies, colistin, a polypeptide antibiotic, was incorporated into either gelatin or PLGA microparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The porosity of these constructs was generated by using a carboxymethylcellulose or gelatin hydrogel as a porogen, and the resulting porosity allowed for greater cumulative release of antibiotic. [7][8][9][10] In these studies, colistin, a polypeptide antibiotic, was incorporated into either gelatin or PLGA microparticles. Colistin was selected due to its efficacy against Acinetobacter baumannii, a commonly multi-drug resistant bacterial strain that has been observed to have increased incidence of infection in traumatic combat wounds [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches have been mainly used for scaffold bioactivation: GFs can be encapsulated in a selected drug delivery system such as a microsphere or nanoparticle formulation, and these can be incorporated into the scaffolds. Alternatively, GFs might be incorporated directly into the scaffold itself (Holland & Mikos, 2006;Holland et al, 2007;Liu et al, 2010b;Luginbuehl et al, 2004;Shi et al, 2011;Uebersax et al, 2009). For example, IGF-1 has been incorporated into biodegradable poly(lactide-co-glycolide) microspheres and used as a treatment for 10-mm segmental tibial defects in sheep (Meinel et al, 2003).…”
Section: Scaffolds As Drug Delivery Systemsmentioning
confidence: 99%